Strategi Fundraising LAZISMU Malaysia dalam Meningkatkan Peran Lembaga Zakat Sebagai Upaya Pengentasan Kemiskinan - Sutrisno, Sutrisno (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to investigate how the fundraising strategies of zakat institutions are implemented, with a case study of LAZISMU Malaysia. This study is qualitative in nature, utilizing a case study approach. The methods employed for data collection include observation, interviews, and documentation. Interviews were conducted with 6 informants consisting of personnel in the Human Resources department, fundraising department, and head of the fundraising department. Data validity was tested using triangulation of sources and triangulation of techniques. The findings of this research indicate that LAZISMU Malaysia has generally implemented fundraising strategies in line with both direct and indirect fundraising methods. Furthermore, these strategies have helped enhance the role of zakat institutions in poverty reduction through various productive zakat programs. However, the research also identified challenges in fundraising implementation, particularly in maximizing fundraising strategies, resulting in Indonesian communities residing around LAZISMU Malaysia being less familiar with LAZISMU. To address these challenges, LAZISMU Malaysia plans to alter its fundraising strategy by conducting educational campaigns targeting the Indonesian community in Malaysia to increase awareness about zakat, infaq, and sadaqah payments.